Implementation and Evaluation of a Pediatric Pain Assessment Educational Program (PPAEP) for Nurses in a Resource‐Limited Setting: A Pilot Study - Kusi Amponsah, Abigail; Hammond, Charles Kumi; Bam, Victoria; Gyamfi, Douglas; Armah, Jerry; Wilson, Dorothy; Annobil, Faithful; Badengo, Daniel Ba‐Eebu; Danquah, Charlotte Boachie; Dompim, Joana Kyei; Axelin, Anna; Nawagi, Faith; et al. (Wiley, 2026)
Nurses play a vital role in pediatric pain assessment and management. However, nurses' limited competencies in pain management have been identified as one of the barriers to optimal pediatric pain care. Therefore, this study aimed to implement and evaluate an educational program and changes in nurses' pediatric pain assessment knowledge and attitudes (PPAKA), self-efficacy, and the program's acceptability. Guided by Kirkpatrick's model of evaluation, a one-group pre-post study was conducted among 20 nurses working at the children's unit of the Kwame Nkrumah University of Science and Technology (KNUST) Hospital in Ghana. The pediatric pain assessment educational program (PPAEP) was delivered to the nurses by a pediatric pain nurse researcher in a one-time training session. Participants' pediatric pain assessment knowledge, attitudes, and self-efficacy were assessed before and after the educational program, whereas the program's acceptability was assessed only after the training session. Wilcoxon signed-rank test was performed to evaluate changes in knowledge, attitudes, and self-efficacy following the educational program. Acceptability was presented using descriptive statistics. A Wilcoxon signed-rank test revealed that nurses' PPAKA scores significantly increased after participating in the educational program (z = −2.514, p = 0.012). The standard PPAKA score increased from 63 at pre-test to 78 at post-test. Participants' self-reported efficacy in assessing pediatric pain was also significantly higher at post-test than at pre-test (z = −3.967, p < 0.001). The standard self-efficacy score increased from 58.6 at pre-test to 87.7 at post-test. Participants were satisfied and gave positive feedback on the program. A brief PPAEP is acceptable among nurses in a resource-constrained setting and is associated with improvement in pediatric pain assessment knowledge, attitudes, and self-efficacy. Future multi-site studies using larger samples and more rigorous designs, such as randomized controlled trials, are needed to evaluate the program's effectiveness.